ESG Score and Cost of Debt: Evidence from Indonesia - Siagian, Valentine; Sinaga, Judith Tagal Gallena; Sinaga, Nensy Dwi Putri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: This study explores the influence of Environmental, Social, and Governance (ESG) practices on corporate debt costs. The primary objective is to determine whether comprehensive ESG adherence can function as a mechanism to reduce financial liabilities by lowering borrowing costs.Design/Methodology/Approach: The research employs a quantitative methodology, using a dataset of ESG scores from 635 firm-year observations in Indonesian data covering 2013-2022, and analyzes it using OLS regression. The analytical approach involves comparing corporate debt costs with overall ESG scores and with the disaggregated ESG scores independently.Research findings: ESG scores are associated with lower debt costs. However, when the components are analyzed separately, only the Governance score shows a statistically significant negative correlation with debt costs. Environmental and Social scores do not demonstrate a meaningful standalone effect. It suggests that creditors place greater emphasis on governance-related factors in assessing credit risk.Theoretical contribution/Originality: This study makes a significant contribution to the literature on sustainable finance by providing empirical evidence of the differential impact of ESG components on corporate financing costs. It advances understanding of how ESG factors, particularly governance, shape firms’ financial outcomes.Practitioner/Policy implication: The results highlight the strategic importance of governance-focused ESG initiatives for firms seeking to lower financing costs. Policymakers and corporate strategists should recognize the value creditors place on governance practices and incorporate this insight into ESG frameworks and disclosure standards.